Efektivitas Implementasi E-Health di Puskesmas Kedungdoro dan Puskesmas Keputih Surabaya - Nabilla Jasmine; Bagus Nuari Harmawan (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
Public service is a primary obligation of the government in organizing activities to meet community needs. The Surabaya City Government is collaborating with the Surabaya City Health Office to create service innovations aimed at improving public health services through E-Government initiatives. One such innovation is E-Health, an online registration service designed to simplify the registration process at hospitals and health centers. This research aims to assess the effectiveness of the E-Health program in Surabaya's health services, based on Mehdi Asgarkhani's (2005) theory of technology-based service effectiveness, which includes information security, impact on jobs and workplaces, impacts on individual rights, Potential Impact On Society and social interactions. Using a qualitative case study approach at Kedungdoro and Keputih community health centers, the findings show that E-Health is effective and facilitates community access to health services. However, ongoing evaluation and optimal improvement of human resources are needed for sustainable E-Health services.